A bootstrap approach for predicting fluoride toxicity in paramedics after occupational methoxyflurane exposure. (30th September 2019) - Allison, Serah J.; Docherty, Paul D.; Pons, Dirk; Chase, J. Geoffrey
Abstract: Background: Methoxyflurane is an anaesthetic that can cause dose-related patient nephrotoxicity. It was withdrawn from anaesthetic use approximately 40 years ago. It is now only administered for analgesia, via inhaler devices. Ambulance officers can be exposed to methoxyflurane vapour during methoxyflurane administration. While extrapolation from data of anaesthetised patients implied occupational exposure was safe, this may be doubtful and requires further verification. Approach — Patient data from four anaesthesia studies were combined. A bootstrap analysis of the combined data was used to form a probabilistic inference of the risk posed to ambulance officers. Findings — Due to extrapolation over 2–5 orders of magnitude of exposure from the source data, there was a very low precision in the likely risk. Both the linear and power law models exhibited non-zero risk, of 8.7% and 0.3% toxicity risk respectively, for a single exposure in the likely occupational range. This suggests that the safety of occupational exposure cannot be firmly established with this type of extrapolation analysis. Furthermore, this approach does not account for repeated exposures, or outlier events. Conclusion: Data from anaesthesia studies is inadequate for extrapolation to occupational exposure. Consequently, risks for ambulance officers need to be reappraised. There is a need for further empirical study to determine the exposure of ambulance officers and other healthcare staff.